Spectrum of pleural effusion etiology revisited in 18-70 years of age group: A tertiary care center-based study of 1000 patients - Rahul Gupta; Anchal Gupta; Mohd Ilyas (Wolters Kluwer Medknow Publications, 2018)
Objective: The main objective study was to evaluate the new-onset cases of pleural effusion with respect to etiology/causation. Materials and Methods: A total of 1000 patients were included in the study aged between 18 and 70 years. The patients with earlier diagnosis of pleural effusion or those who had undergone thoracocentesis were excluded from the study. All the patients were subjected to thorough clinical examination, chest radiography, chest and abdominal sonography, pleural fluid analysis, and pleural fluid cytology, and in select cases, pleural biopsy was done. The results were assimilated and tabulated, observations thereby drawn by. Results and Observations: Out of total 1000 patients, 69.5% had tuberculosis followed by malignancy (16%) with the systemic causes forming about 15% bulk of the patients with pleural effusion. It was found more in males, associated with smoking, and majority of patients had unilateral effusion. Eighty-nine percent of patients had exudative effusion. Conclusion: The results of the study revealed that tuberculosis is still the most common cause of pleural effusion and efforts need to be stepped up to control tuberculosis. The national programs for control of tuberculosis need to be revisited to assess the magnitude of the problem, and the patients need to be counseled for the compliance of the therapy. Furthermore, malignancy is trending upward in the etiology of pleural effusion.